Våldtäktsoffrets psykiska lidande som faktor vid rubricering och straffvärdebedömning – En utredning om straffrättsregleringens och rättstillämpningens hänsyn till psykiskt lidande med utgångspunkt i tvärdisciplinär forskning - Frändestam,Moa (2022)
Interests and needs of victims of crime have received increased attention in recent years. Particularly, the awareness has risen regarding the extensive psychological harm victims are caused. Rape, which is regulated in 6 ch. 1 § BrB, constitutes a clear example of a crime which frequently entails considerable psychological effects on victims. This essay has aimed to clarify if and how the psychological suffering of victims is regarded in the classification and penal value assessment (29 ch. 1-3 §§ BrB) related to rape. To achieve this purpose, the essay has examined which opportunities are provided by law to pay regard to mental suffering within the mentioned stages of assessment, how the mental suffering is considered by the district courts in their application of the law, and lastly how the aforementioned findings appear in relation to cross disciplinary research. The questions are answered using the theoretical framework of victimology and therapeutic jurisprudence. Victimology aims to enhance the victims’ needs and interests in various parts of the legal system. Therapeutic jurisprudence underlines the importance of cooperation between law and social sciences to achieve a more efficient and substantiated legal system. In the essay, both legal dogmatic method and empirical method have been used. The results show that the opportunities of paying regard to psychological suffering are extensive. Within the classification process, the circumstance is a factor when determining if the deed falls within the scope of the rape provision, as well as to determine it’s severity. Within the penal value assessment, the psychological suffering constitutes a relevant harm, danger or violation for rape. The suffering is also given a certain breakthrough through the aggravating circumstances in 29 ch. 2 § BrB. Lastly, the legal concept of penal value has been given an extensive scope, implying great possibilities for the consideration of mental suffering. However, two limitations are identified – the principle that the penal value must solely be based on circumstances surrounding the crime, and the requirement that the observed circumstance must be encompassed by the perpetrator's intent. The overall assessment, however, implies that most types of psychological suffering will be possible to consider, given that the circumstances suggest the perpetrator realized that such an effect would occur. The case analysis implies certain flaws. The district courts generally do not present the basis for their assessments, or when they do, very briefly. Even in cases where the courts find the psychological suffering proved, such aspects appear to be disregarded in the penal classification and the penal value assessment. The intention that the legislator and the public investigators have expressed, to implement to a greater extent the perspective of psychological harm in relation to sexual crimes, does not appear to have succeeded. Seemingly, this can be associated with the current regulation and legislative history, which only indirectly and partially mentions the psychological suffering. Lastly, the essay concludes with a recommendation of certain legislative amendments. Psychological suffering should be mentioned directly and explicitly in the law. This would clarify its relevance and most likely lead to a more stringent application of law. Furthermore, it would better correspond to victimological research in accordance with the fundamentals of therapeutic jurisprudence.
Keywords: allmän rättslära; straffrätt; psykiskt lidande; viktimologi; terapeutisk juridik; tvärdisciplinär forskning; våldtäkt; sexualbrott